Problem-Based Learning Assisted by GeoGebra to Improve Students’ Mathematical Understanding - Keni Eviliasani; Jozua Sabandar; Nelly Fitriani (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to develop teaching materials to improve the mathematical understanding of the Pythagorean theorem material by using the development of teaching materials through the GeoGebra-assisted Problem Based Learning (PBL) approach. This study uses the Borg Gall model's research and Development (RnD) development method with the Borg Gall model. The researchers collected data through observation, questionnaires, interviews, and tests of mathematical understanding abilities. The population in this study was 80 students of Madrasah Tsanawiyah class VIII, with 30 students in a limited trial and 50 students in a broad trial. Data is processed using descriptive and inferential statistics. This research produced a teaching material with a Problem Based Learning approach assisted by Geogebra software on the Pythagorean theorem material and indicates that there is an increase in students' mathematical understanding abilities after being given learning using GeoGebra-assisted PBL approach teaching materials.